Urbanization and spatial connectivity in Ethiopia: Urban growth analysis using GIS - Schmidt, Emily; Kedir Jemal, Mekamu (International Food Policy Research Institute, 2009)
In comparison to other African countries, Ethiopia has a low urbanization rate. According to the World Bank World Development Report (WDR) 2009, Sub-Sahara Africa is 30% urbanized, whereas Ethiopia is only 10.9% urbanized. Urbanization rates differ according to methodologies and data base utilized: the United Nations classifies Ethiopia as 14.9% urban, while the Central Statistical Agency of Ethiopia reports a 16% urbanization rate. In an effort to standardize and measure Ethiopian urbanization over time, we use the WDR agglomeration index methodology which incorporates a series of GIS data and analyses including: travel time rasters, population density (namely GRUMP and LandScan gridded population), and other nationally collected biophysical and infrastructure variables. We spatially allocate urban versus non-urban areas by creating specific thresholds following two criteria whereby locations are categorized as urban if populations have: a population density greater than 150 people per km2; and are located within 1 hour travel time from a city of at least 50,000 people. Utilizing road and population data from different years between 1984 and 2006, we are able to model growth in urbanization and reductions in remoteness over time. Using the agglomeration index methodology, we find that the overall share of urban population increased from 3.7 percent in 1984 to 14.2 percent in 2007. The results indicate substantial improvements in travel time between urban centers over the past two decades, though a large share of the population still resides more than 10 hours travel time from an urban center.